Investigation within the Scope of Tax Procedure Law and Financial Reporting Standards for Large and Medium Sized Enterprises of Foreign Trade Transactions - Öztürk Yöndemli, Seçil (Journal of Applied And Theoretical Social Sciences, 2021)
Foreign trade includes export and import transactions, which express the trade of goods and services between countries. The impact of foreign trade on the country's economy is undeniable. In parallel with the increasing foreign trade volume worldwide, there is an increase in foreign trade transactions in our country. A significant part of foreign trade transactions in our country are carried out by large and medium-sized enterprises. The answers to the questions of how these enterprises will account for their foreign trade transactions and report them in their financial statements differ according to the standards, principles and regulations on which they are based. The aim of this study is to examine the accounting principles of foreign trade transactions of enterprises in terms of Financial Reporting Standards of Large and Medium Sized Enterprises and tax legislation. Within the scope of the study, similar and different applications between accounting standards and tax legislation were put forward in the theoretical framework.